Chitosan based in situ forming Polyelectrolyte Complexes: A Novel approach for Designing Sustained Release Formulation - Malik, Ajay; Verma, Navneet; Sharma, Vijay; Sahani, Vibhu (Journal of Neonatal Surgery, 2025)
The present study is an attempt to develop and evaluate the sustained release tablet formulations (oral) of paracetamol utilizing chitosan based in situ forming polyelecrolyte complex as retardant polymer. The traditional method of wet granulation was used to create various formulations. A 1% w/w solution of chitosan in 1% acetic acid (cooled to about 4 oC and neutralized) was used as binder to granulate the drug mixed with anionic polymer (sodium starch glycolate) and other excipients. A number of characteristics were assessed for the tablets, including thickness, hardness, friability, drug content, and uniformity of weight. The in vitro drug release studies were conducted for 12 hrs, in 500 ml of HCl + KCl buffer [(pH 1.5) for 2 hr], for 8 hr in mixed phosphate buffer (pH 6.8) and again for 2 hr at pH 7.5 utilizing mixed phosphate buffer using USP type II apparatus running at 50 rpm. The pharmacokinetic parameters were examined by using various mathematical models (zero order, Higuchi, first order, Korsmeyer – Pepps equations and Hixson – crowell) to investigate and elucidate the mechanism of drug release from the various formulations/ tablets. The drug release studies confirmed the sustained release of drug for 12 hrs. The polyelectrolyte complex formation (in situ) between anionic polymers and chitosan had been revealed by XRD studies of polyelectrolyte complex gels